Knowledge, Attitudes, and Perceptions of COVID-19 Among Healthcare and Non-Healthcare Workers in Sub-Saharan Africa: A Web-Based Survey - Ekpenyong, B.N.; Osuagwu, U.L.; Miner, C.A.; Ovenseri-Ogbomo, G.O.; Abu, E.K.; Goson, P.C.; Langsi, R.; Nwaeze, O.; Chikasirimobi, T.G.; Charwe, D.D.; Mashige, K.P.; Oloruntoba, Richard; et al. (MARY ANN LIEBERT, INC, 2021)
Due to the current COVID-19 pandemic and associated high mortality in sub-Saharan Africa, there is panic among healthcare workers because of the higher risk of being infected. This study compared knowledge, attitudes, and perceptions of COVID-19 among healthcare workers (HCWs) and non-healthcare workers (non-HCWs) and examined common associated factors. A web-based cross-sectional study of 1,871 respondents (430 HCWs and 1,441 non-HCWs) was conducted while lockdown measures were in place in 4 regions of sub-Saharan Africa. Data were obtained using a validated self-administered questionnaire via an online survey platform. Mean scores were calculated and summarized using a t test for both groups. Multivariate linear regression analysis was conducted to assess the unadjusted (B) and adjusted coefficients (β) with a confidence interval (CI) of 95%. The mean scores were slightly higher among HCWs than non-HCWs, but not statistically significant. Being worried about contracting COVID-19 was the only common factor associated with knowledge, attitudes, and perceptions between the 2 groups. Knowledge of COVID-19 was associated with attitudes and perceptions between the 2 groups. Other significant associated factors were: the sub-Saharan Africa region, ages 29 to 38 years (β = .32; 95% CI, 0.04 to 0.60 for knowledge among non-HCWs), education (β = -.43; 95% CI, -0.81 to -0.04; and β = -.95; 95% CI, -1.69 to -0.22, for knowledge among non-HCWs and HCWs, respectively), practice of self-isolation (β = .71; 95% CI, 0.41 to 1.02 for attitude among non-HCWs and HCWs (β = .97; 95% CI, 0.45 to 1.49), and home quarantine due to COVID-19, in both groups. Policymakers and healthcare providers should consider these factors when targeting interventions during COVID-19 and other future pandemics.